Case Report: A Novel IL2RG Frame-Restoring Rescue Mutation Mimics Early T Cell Engraftment Following Haploidentical Hematopoietic Stem Cell Transplantation in a Patient With X-SCID - Steininger, Jolanda; Leiss-Piller, Alexander; Geier, Christoph B.; Rossmanith, Raphael; Elfeky, Reem; Bra, David; Pichler, Herbert; Lawitschka, Anita; Zubarovskaya, Natascha; Artacker, Gottfried; Matthes-Leodolter, Susanne; Eibl, Martha M.; et al. (Frontiers in Immunology, 2021)
Mutations of the interleukin 2 receptor γ chain (IL2RG) result in the most common form of severe combined immunodeficiency (SCID), which is characterized by severe and persistent infections starting in early life with an absence of T cells and natural killer cells, normal or elevated B cell counts, and hypogammaglobulinemia. X-SCID is commonly fatal within the first year of life, unless the immune system is reconstituted by hematopoietic stem cell transplantation (HSCT) or gene therapy. We herein describe a male infant with X-linked severe combined immunodeficiency (X-SCID) diagnosed at 5 months of age. Genetic testing revealed a novel C to G missense mutation in exon 1 resulting in a 3’ splice site disruption with premature stop codon and aberrant IL2 receptor signaling. Following the diagnosis of X-SCID, the patient subsequently underwent a TCRαβ/CD19-depleted haploidentical HSCT. Post transplantation the patient presented with early CD8+ T cell recovery with the majority of T cells (>99%) being non-donor T cells. Genetic analysis of CD4+ and CD8+ T cells revealed a spontaneous 14 nucleotide insertion at the mutation site resulting in a novel splice site and restoring the reading frame although defective IL2RG function was still demonstrated. In conclusion, our findings describe a spontaneous second-site mutation in IL2RG as a novel cause of somatic mosaicism and early T cell recovery following haploidentical HSCT.